2002
DOI: 10.1002/j.1467-8438.2002.tb00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Cults and the Family

Abstract: In recent years an increasing number of therapists have come into contact with ex‐cult members. Consequently there has been a renewed interest in various facets of intervention with this population. However, the effects of cult affiliation and disaffiliation on the cult member's family are not as well documented, particularly in Australia. This paper offers an overview of cult dynamics as well as some of the difficulties experienced by families whose loved one has had cult involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This observation challenges much of the current thinking on NRMs, in particular as it relates to the majority of the available support offered to former members by health professionals. The primary treatment model employed by those who work with former members pertains to helping the former members resolve or undo the negative impacts of having been brainwashed, with a focus on assisting former members in restoring their former identities (Dowhower, 1993;Halperin, 1993;Langone, 1993;Rohmann, 2006;Walsh & Bor, 1996;Ward, 2000Ward, , 2002. In line with previous observation, considering the many positive reported by the participants, a treatment model that assumes significant negative impacts of membership may not be the most appropriate model, and a more general counseling approach that is focused on the management of issues such as stress, grief, and loss may be more suitable in helping former members negotiate a transition following exit (Coates, 2009;Healy, 2010Healy, , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…This observation challenges much of the current thinking on NRMs, in particular as it relates to the majority of the available support offered to former members by health professionals. The primary treatment model employed by those who work with former members pertains to helping the former members resolve or undo the negative impacts of having been brainwashed, with a focus on assisting former members in restoring their former identities (Dowhower, 1993;Halperin, 1993;Langone, 1993;Rohmann, 2006;Walsh & Bor, 1996;Ward, 2000Ward, , 2002. In line with previous observation, considering the many positive reported by the participants, a treatment model that assumes significant negative impacts of membership may not be the most appropriate model, and a more general counseling approach that is focused on the management of issues such as stress, grief, and loss may be more suitable in helping former members negotiate a transition following exit (Coates, 2009;Healy, 2010Healy, , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that most psychotherapy work with fundamentalist families within the National Health Service at least will take place at this point in the family life cycle. The fragility of this transitional life stage may also explain why late adolescence and early adulthood are the time associated with most religious conversions (Ward, 2002) and radicalisation. Young adults may struggle with true independence and religious community may act as a replacement family (Sirkin, 1990).…”
Section: Ethical Considerations In the Context Of Religious Fundamentmentioning
confidence: 99%
“…There is little literature examining the impact of cults on families and how the conversion of a family member influences outgroup members’ lives and well-being (Addis et al, 1984; Goldberg & Goldberg, 1989; Langone, 1990; Schwartz, 1983; Singer, 1986; Ward, 2002; Whitsett & Kent, 2003). Most studies on the topic are decades old, are based on experiences observed in clinical practice, and focus almost exclusively on the parents of young cultists, thus ignoring other relationships of interest (such as spouses, partners, and children).…”
mentioning
confidence: 99%
“…Moreover, the family is typically the main source of support for recovery, given that relatives are frequently responsible for initiating requests for professional help and advice (Dubrow-Marshall et al, 2017; Rousselet et al, 2017; Singer, 1986). Families also witness radical changes in their loved one’s behavior, personality, and customs, which is increasingly perceived as more distant, apathetic, and conflictual (Langone, 1985; Singer, 1986; Ward, 2002). In some cases, parents of young cultists report feelings of frustration and helplessness, sentiments that manifest as feelings of sadness, loss, and guilt, leading to depression or physical problems (Addis et al, 1984; Bloch & Shor, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation